THE EFFECT OF GOOD CORPORATE GOVERNANCE (GCG) ON COMPANY VALUE: (An Empirical Study on Mining Companies Listed on the Indonesia Stock Exchange) - Ruly Priantilianingtiasari (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
Purpose – This research aims to obtain evidence related to good corporate governance which was measured from the variable of managerial ownership, institutional ownership, independent commissioner, and audit committee that affects the firm value as a reflection of firm performance. Design/methodology/approach – The type of research used is descriptive and associative research. The population in this research are mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The purposive sampling method is used to get the samples with the criteria of mining companies listed on the Indonesia Stock Exchange (IDX) from 2015-to 2019, publishing annual reports consistently and having complete data related to research variables. Findings – From the results of the research analysis, it was found that based on the F test of Managerial Ownership, Institutional Ownership, Independent Commissioners, and Audit Committee simultaneously had a significant positive effect on firm value. Based on the results of hypothesis testing using the t-test, it was concluded that Managerial Ownership, Independent Commissioner partially had a negative and significant effect on firm value, while Institutional Ownership and Audit Committee partially had no significant effect on firm value. Research limitations/implications – This research only takes some of the research and expects further research to sample that which is broad in vulnerable time study. And the research for measuring is limited, so it would add another variable to the equation in the future. Originality/value – The Audit Committee does not affect firm value. It is possible that the company only applies to comply with formal GCG. So the existence of the audit committee does not indicate an improvement in the company’s performance. Keywords: Good Corporate Governance; Company Value; managerial ownership; institutional ownership; independent board of commissioners; audit committee Paper type: Case Study